Visible color changes estimation in colorimetric determination of chromium (VI) using polymeric sensors; Acta IMEKO; Vol. 5, iss. 3: Introduction to the Special Section TC21 of the XXI IMEKO World Congress 2015 - Gavrilenko N. A. Natalia Airatovna; Muravyov (Murav’ev) S. V. Sergey Vasilyevich; Saranchina N. V. Nadezhda Vasilievna; Sukhanov A. V. Aleksey Viktorovich (2016, 2016)
Title screen